PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP CITRA MEREK DAN MINAT BELI PADA PRODUK KOSMETIK WARDAH - Adriyati, Rosmaya; Indriani, Farida (Diponegoro Journal of Management, 2017)
In obtaining information about a product, the consumer is no longer limited to the information from the manufacturer. The Information of the product can be obtained from other consumers personally as known as word of mouth. Along with the development of internet technology, word of mouth communication is not only done in a personal but it can be done with a broader range called electronic word of mouth. The concept of electronic word of mouth in the form of an opinion regarding a product or company that expressed by actual consumer via social media that can be either positive or negative reviews, so it can affect the prospective consumers glance towards the brand image and its impact on purchase intention of product. This study aims to determine the effect of electronic word of mouth on the brand image and purchase intention, especially wardah cosmetics products that are currently reviewed by social media.This research used purposive sampling technique which is included in non-probability sampling method, by spreading questionnaires to 100 respondents of young women in Semarang who aware about electronic word of mouthÂ  with age of 15-29 years. Collected data were analyzed with several tests: validity, reliability, normality, heteroskedasidity, statistical t test, statistical f test, coefficient of determination test, multiple regression analysis, and sobel test using IBM SPSS 23 for windows software application.The results indicated that electronic word of mouth has significant influence on brand image and purchase intention. While the brand image as an intervening variable hasÂ  significant influence on purchase intention as a partial mediation.